Unsuspected Paraganglioma—Infratemporal Fossa - Nikhat Sultana J; Shekhar R. Gurrala; Lakshman K. Kommula; Gnana R. Boola (Journal of Neuroanaesthesiology and Critical Care, 2020)
Paraganglioma of the infratemporal fossa is exceedingly rare, with no more than a handful of documented cases. Undiagnosed paraganglioma poses a great challenge. We present a 39-year-old hypertensive female, who presented with giddiness and headache for 3 months and four episodes of syncope over 3 months. CT and MRI revealed an enhancing infratemporal region space-occupying mass close proximity to petrous carotid artery. Intraoperatively, the patient had hemodynamic instability (tachycardia and hypertension) when the mass was surgically manipulated. Diagnosis of paraganglioma was suspected, based on hemodynamic instability, which was later confirmed by histopathology. Undiagnosed paraganglioma pose a great challenge to the anesthetic management. Low-threshold of suspicion has to be there to avoid significant morbidity and mortality.